Treatment of haemophilia A in Tunisia: efficacy and inhibitor study - Houissa, B.; Mliki, ML.; Abdelkafi, S.; Bouslama, M.; Zaïer, M.; Mahjoub, T.; Kortas, M.; Ghachem, L.; Yacoub, S. (Hämostaseologie, 2003)
Cryoprecipitate is the principal type of factor VIII (FVIII) concentrate used for treating haemophilia A in Tunisia. Allergic reactions, viral transmission, and inhibitor formation remain the most serious complications of FVIII therapy. The aims of the study presented here were to evaluate the efficacy of FVIII therapy, to investigate the inhibitor prevalence, and the factors which may affect inhibitor formation in our haemophilia A patients. Plasma samples were screened for FVIII inhibitors by the Bethesda method. 30 minutes FVIII recovery was also determined for each patient. In this prospective study, 18 previously treated haemophilia A patients, four with severe (FVIII concentration <2%) and 14 with moderate haemophilia, were closely followed up during administration of 223 FVIII concentrates (cryoprecipitate and/or fresh frozen plasma). The median age of the patients involved in the study was 13.5 years (range 5 to 53).Clinical response to FVIII was consistently good to excellent. In the majority of cases, actual and predicted FVIII recovery correlated’ well. Adverse reactions were not observed. Five patients, aged less than 18 years and minimally treated (<36 FVIII exposure days), were found to have low titre FVIII inhibitors (<10 Bethesda units) at the end of the study. Inhibitor activity was detected in one patient with severe and in four patients with moderate haemophilia. In conclusion, FVIII therapy was effective, well tolerated, and low titre inhibitors identified did not preclude continued on demand FVIII therapy. Our study has also demonstrated that patients’ age and treatment regimen do not affect inhibitor formation. Further studies are necessary to confirm these findings.
Keywords: Haemophilia A; factor VIII; recovery; inhibitors